Up-conversion luminescence in Yb3+-Er3+/Tm3+ co-doped Al2O3-TiO2 nano-composites - Mokoena, Teboho Patrick; Linganiso, Ella Cebisa; Kumar, Vinod; Swart, Hendrik C.; Cho, So-Hye; Ntwaeaborwa, Odireleng Martin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2017)
The sol gel method was used to prepare rare-earths (Yb3+-Er3+ and Yb3+-Tm3+) co-doped A1(2)O(3)-TiO2 nano composite powder phosphors and their up-conversion luminescence properties were investigated. Mixed oxides of titania (TiO2) rutile phase and an early stage crystallization of alumina (A1(2)O(3)) phase were confirmed from the X-ray diffraction data with the average crystallite size of similar to 36 nm. The rutile phase TiO2 was further confirmed by selected area diffraction analysis of the composites. Microscopy analysis showed interesting rod-like morphologies with rough surfaces indicating that a spherulitic growth process took place during the crystal growth. Photoluminescence characterization of the phosphors was carried out under near infra-red excitation at 980 nm and the prominent emission bands were observed in the visible region at 523, 548 and 658 nm for the Yb3+-Er3+ co-doped systems. Emission in bands extending from the visible to near infra-red regions were observed at 480, 650, 693 and 800 nm for the Yb3+-Tm3+ co-doped systems. These upconverted emissions and energy transfer mechanisms taking place are discussed in detail. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: SOL-GEL; ER3+-DOPED TIO2; EMISSION; ABSORPTION; SIZE; RED